CAUSE-EFFECT RELATIONSHIP BETWEEN GROWTH AND PROFITABILITY: EVIDENCE FROM MANUFACTURING COMPANIES LISTED IN COLOMBO STOCK EXCHANGE - Sanjaya, R. A. A.; Jayasiri, N. K. (University of Jaffna, 2019)
The objective of this study is to identify the Cause-effect Relationship between Growth and Profitability conducted for twenty listed manufacturing companies in Colombo Stock Exchange of Sri Lanka, for five years of the period (2009/10 to 20013/14). Independent variable of Growth measured by SGR and AGR while dependent variable of Profitability measured by NPR and ROA. E-views statistical package was used for analysis based on the significant value of t-test, Coefficient of Co-relation from Panel Regression model, and Descriptive statistics. Research objectives of the study are, to empirically test the relationship between firm's growth and profitability, as measured by ROA and Net profit, to find out the effect of Sales growth on ROA and Net profit, and to examine the effect of Assets growth on the ROA and Net profit. According to the findings of the research analyze, first and third objectives achieved by the researcher. Study indicates that both Lag models of Pooled Regression and Random Effect model show that Sales Growth has not any significant relationship on Net Profit and Return on Assets. Therefore, one of the Growth measurements of Sales Growth did not show any relationship on Profitability as measured by Net Profit and Return on Assets. However, Assets Growth has a significant positive relationship on Net Profit and Return on Assets, therefore, another Growth measurement of Assets Growth show Positive significant relationship on Profitability as measured by Net Profit and Return on Assets. Therefore, the researcher can say, Independent variable of Firms' Growth positively impact on the dependent variable of Firms' Profitability when the firms' Growth measured by the Assets Growth.
Keywords: growth; manufacturing companies; profitability